Prawno-konstytucyjne implikacje wystąpienia Wielkiej Brytanii z Unii Europejskiej – perspektywa brytyjska - Łukasz Danel (Ksiegarnia Akademicka Publishing, 2019)
Legal and Constitutional Implications of the United Kigdom’s Withdrawal From the European Union – the British Perspective The article is dedicated to the issue of legal and constitutional implications of Brexit seen from the perspective of United Kingdom of Great Britain and Northern Ireland. The author advances a thesis that the withdrawal from the European Union will be the most complicated legal operation in the history of the British state as for more than 40 years United Kingdom has been a part of European Communities (today’s European Union) which affected greatly the British legal system. In order to prove the thesis the author analyses the political and legal discussion around the European Union (Withdrawal) Bill 2017‑2019 that is supposed to repeal the European Communities Act 1972 and transpose the existing EU Law into UK law. The bill is controversial – especially the provisions known as Henry VIII clauses that create special powers for the government to make secondary legislation.